PERSPEKTIF GURU DI SEKOLAH INDONESIA JEDDAH TERHADAP PEMBELAJARAN BERDIFERENSIASI - Rofiah, Nurul Hidayati; Setiawati, Nelly; Nofikusumawati Peni, Nur Robiah; Biddinika, Muhammad Kunta; Subekti, Dewi Ani; Alghiffari, Eka Kevin; Fitriah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract This community activity aims to improve the understanding and skills of teachers at Jeddah Indonesia Schools related to the implementation of differentiated learning strategies in the classroom. The study gathers data through a questionnaire distributed to the 37 teachers across various grade levels and subjects at school Indonesia in Jeddah relatedto differentiated learning. The result analysis is based on key themes, such as teachers^ understanding of Differentiated Learning and student^s learning styles, challenges encountered toward the assessment, perceptions of its effectiveness in meeting students^ diverse learning needs, and the usage of learning technology facilitating differentiated learning. The findings provide valuable insights into the practical application of Differentiated Learning in the Indonesian Jeddah School, shedding light on the alignment ofteacher beliefs and classroom practices. The study contributes to the growing body of research on educational practices in international contexts and offers recommendations for enhancing the integration of Differentiated Learning approaches. Understanding teacher perspectives on Differentiated Learning is crucial for fostering more inclusive and effective pedagogical methods that cater to the diverse needs of students in culturally diverse settings like the Indonesian Jeddah School. Abstrak Kegiatan pengabdian ini bertujuan untuk meningkatkan pemahaman dan keterampilan guru guru di Sekolah Jeddah Indonesia terkait dengan penerapan strategi pembelajaran berdiferensiasi di kelas. Studi ini mengumpulkan data melalui kuesioner yang dibagikan kepada 37 guru di berbagai tingkatan kelas dan mata pelajaran di sekolah Indonesia di Jeddah terkait dengan pembelajaran berdiferensiasi. Analisis hasil didasarkan pada tema- tema utama, seperti pemahaman guru tentang pembelajaran berdiferensiasi dan gaya belajar siswa, tantangan yang dihadapi dalam penilaian, dan persepsi keefektifan penggunaannya dalam memenuhi kebutuhan belajar siswa yang beragam, serta penggunaan teknologi yang memfasilitasi pembelajaran berdiferensiasi. Temuan dari penelitian ini memberikan wawasan berharga ke dalam aplikasi praktis Pembelajaran Berdiferensiasi di Sekolah Jeddah Indonesia, menyoroti keselarasan keyakinan guru dan praktik kelas. Studi ini berkontribusi pada pertumbuhan penelitian tentang praktik pendidikan dalam konteks internasional dan menawarkan rekomendasi untuk meningkatkan integrasi pendekatan pembelajaran berdiferensiasi. Pemahaman perspektif guru tentang pembelajaran berdiferensiasi sangat penting untuk mengembangkan metode pedagogis yang lebih inklusif dan efektif yang memenuhi beragam kebutuhan siswa dalam lingkungan yang beragam budaya seperti Sekolah Jeddah Indonesia.